2021
DOI: 10.1155/2021/8896896
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-Analysis of Good Self-Care Practice among People Living with Type 2 Diabetes Mellitus in Ethiopia: A National Call to Bolster Lifestyle Changes

Abstract: Background. Self-care practice is the mainstay of management for good glycemic control. Despite the presence of a few pocket studies, no comprehensive study was conducted in Ethiopia to demonstrate the overall good self-care practice among diabetic patients in Ethiopia. Therefore, we intended to conduct this systematic review and meta-analysis to estimate the overall good self-care practice among people living with type 2 diabetes mellitus (T2DM) in Ethiopia. Methods. We systematically searched PubMed, Scopus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 45 publications
2
18
2
Order By: Relevance
“…The prevalence of dyslipidemia, among DM patients, is 67.1% in China [ 26 ], 86% in Bangladesh [ 27 ], 88.9% in Thailand [ 28 ], and 89% in India [ 29 ] whereas, in Ethiopia, hypertriglyceridemia ranges from 14.2% [ 30 ] to 72.5% [ 31 ]. Apt management is essential [ 32 ] which is expensive in resource-limited settings like Ethiopia. Hence, measuring the prevalence and directing this scarce resource towards its prevention is the best solution.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of dyslipidemia, among DM patients, is 67.1% in China [ 26 ], 86% in Bangladesh [ 27 ], 88.9% in Thailand [ 28 ], and 89% in India [ 29 ] whereas, in Ethiopia, hypertriglyceridemia ranges from 14.2% [ 30 ] to 72.5% [ 31 ]. Apt management is essential [ 32 ] which is expensive in resource-limited settings like Ethiopia. Hence, measuring the prevalence and directing this scarce resource towards its prevention is the best solution.…”
Section: Introductionmentioning
confidence: 99%
“…Adherence to self-care behaviour prevents T2DM-associated morbidities and mortalities [ 14 , 15 ]. The systematic reviews that included studies from Ethiopia [ 22 , 23 ], Sub-Saharan Africa [ 24 ], and LMICs [ 25 ] reported the poor practice of self-care behaviours among the people with T2DM and stressed the need for developing and implementing interventions to improve self-care behaviour. South Asians are at higher risk of developing NCDs, including type 2 diabetes [ 5 ], and the health care resources in this region are limited [ 128 , 129 ].…”
Section: Discussionmentioning
confidence: 99%
“…Health workers should improve patient self-care practices to better control plasma glucose and prevent complications related to diabetes mellitus. 23 Good knowledge about diabetic wound care can improve the patient's selfcare status regarding diabetic wound care. 24 Self-care has a very useful value for people with DM.…”
Section: Discussionmentioning
confidence: 99%